Role of the ACTH test and estimation of a safe dose for high potency steroids in vitiligo: A prospective randomized study - Alberto de la Fuente-García; Minerva Gómez-Flores; Leonardo Mancillas-Adame; Jorge Ocampo-Candiani; Oliverio Welsh-Lozano; Jesús Zacarías Villarreal Pérez; José Gerardo González-González; Fernando Lavalle-González (Wolters Kluwer Medknow Publications, 2014)
Background: Topical corticosteroids are used as first line of therapy for vitiligo, although side effects such as adrenal insufficiency are possible. Objectives: To establish the role of ACTH test before, during, and after treatment with high potency topical steroids; to determine if adrenal insufficiency occurs secondary to the use of high potency topical steroids in patients with vitiligo and intact cutaneous barrier; and also to determine response to treatment and side effects. Materials and Methods: Forty-four adults with non-segmental vitiligo affecting 20% or less of the body surface area were included and randomized to receive topical clobetasol propionate 0.05% cream (group 1) or placebo (group 2) for 12 weeks, with a maximum dose of 50 g per week. The placebo group was crossed over after week 6 and started on clobetasol until completion of the study. Serum cortisol levels with the 1 μg ACTH test were determined at baseline and on weeks 6 and 12. Results: No adrenal insufficiency was detected nor statistical significance was achieved when comparing cortisol levels between and within the groups at baseline and weeks 6 and 12. Group 1 had a better response to therapy but with more side effects. Conclusions: Doses of 50 g or less per week of clobetasol during a period of 12 weeks are safe on adult vitiligo patients, although local side effects are possible. Repigmentation rates were incomplete with single steroid therapy, making combined therapy a better option.